The Bankruptcy of Jet Airways in India - Ahmed, Jashim Uddin; Mazid, Tasfia; Ahmed, Asma; Anika, Farzana Haque (IIUM Journal of Case Studies in Management, 2020)
This is a bankruptcy case study of carrier Jet Airways in India. Jet Airways was considered as a major airline in Indiaâ€™s aviation industry. Its daily operation was more than 400 flights to 71 destinations across the world. Jet Airways provided their services to 47 local destinations. Moreover, they also offered international flights to 24 destinations around Asia, Europe, Southern Africa, and North America. Jet Airways had diversified fleets.Â Afterwards, the company became the dominator of the airlines market in the domestic sector by holding a market share of 27 per cent. But the situation changed for the company during the financial crisis of 2010 â€“ 2013, which has changed the customer pattern in the aviation industry. Jet Airways lost its domestic position and also was unable to compete with international players. It has incurred continuous losses in the past nine years consecutively, and its huge debt has destined it towards bankruptcy in June 2019. While having huge liquidation crisis, Jet Airways has invested lots of money for acquiring Air Sahara which is a low-cost carrier. They intended to compete with the dominant industry trend of low budget airways. But this decision has inflated their debt burden. Finally, Jet Airways became bankrupt. In 2019, Reliance Industries and Tata Group has showed their interests to invest at Jet Airways. Jet was waiting for their decision to save the company from bankruptcy, but global pandemic COVID-19 has left no hope for Jet Airways. Air travel was almost stopped due to COVID-19 pandemic and thus, the airline industry has faced the hardest hit among all other industries.